Removal of lead and bisphenol A using magnesium silicate impregnated palm-shell waste powdered activated carbon: Comparative studies on single and binary pollutant adsorption - Choong, C.E.; Ibrahim, S.; Yoon, Y.; Jang, M. (Elsevier, 2018)
In this work, palm shell waste powder activated carbon coated by magnesium silicate (PPAC-MS) were synthesized by the impregnation of magnesium silicate (MgSiO3) using economical material (silicon dioxide powder) via mild hydrothermal approach for the first time. As an effective adsorbent, PPAC-MS simultaneously removes BPA and Pb(II) in single and binary mode. Surprisingly, PPAC-MS exhibited a homogeneous thin plate mesh-like structure, as well as meso- and macropores with a high surface area of 772.1 m2 g−1. Due to its specific morphological characteristics, PPAC-MS had adsorption capacities of Pb(II) as high as 419.9 mg g−1 and 408.8 mg g−1 in single mode and binary mode based on Freudliuch isotherm model while those for BPA by PPAC-MS were 168.4 mg g−1 and 254.7 mg g−1 for single mode and binary modes corresponding to Langmuir isotherm model. Experiment results also indicated that the synergistic removal of BPA occurred because the precipitation process of Pb(II) leads to the co-precipitation of BPA with Pb(OH)2 compound. PPAC-MS showed a good reusability for 5 regeneration cycles using Mg(II) solution followed by thermal treatment. Overall, PPAC-MS has a high potential in the treatment process for wastewater containing both toxic heavy metals and emerging pollutants due to its high sorption capacities and reusability.